The The Influence of Accountability, Transparency, and the Role of Village Apparatus on the Management of Village Revenue and Expenditure Budget - Andriyanti Andriyanti; Dhian Andanarini Minar Savitri (UNIB Press, 2024)
Finding out how local appliances, accountability, and openness affect revenue budget management and village purchases in Temanggung's Kedu area is the primary goal of this study. This research makes use of quantitative data, which is gathered from the responses of respondents via questionnaires that are sent out on the village devices. Eleven hundred and twelve people from fourteen different offices in the Kedu district participated in the survey, including the village chief, secretary, financial officer, planner, enterprise and general manager, and welfare officer. The survey was conducted in the district of Kedu. This research employs purposive sampling in its sampling procedures. Using SPSS, the researchers in this study conducted a double regression analysis on the collected data. The study's findings reveal that 1) accountability greatly benefits APBDes management, 2) transparency greatly benefits APBDes management, and 3) the administrator of APBDs is greatly influenced by the role of village authorities. The findings of the determination coefficient show that independent variables affect dependent variables by 71.9%, while other variables or factors impact the remaining 28.1%.